Powdery Mildew of Strawberries - Natalia A. Peres; James C. Mertely (EDIS)
Powdery mildew, caused by Sphaerotheca macularis, occurs in most areas of the world where strawberries are grown. This is document PP-208 a publication of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Publication date: March 2005.